Negotiating Indonesian Cultural Identity in Arabic Subtitle Translation of Dear David - Waviq Alfiana Irianti; Sajarwa (LISANIA: Journal of Arabic Education and Literature, 2025)
Cultural translation in film is a process of negotiation aimed at balancing the accuracy of the source culture with acceptability in the target culture. This study examines how Indonesian cultural identity is negotiated in the subtitle translation of the film Dear David from Indonesian into Arabic. The research employs a qualitative descriptive method with a comparative and interpretative approach. The analyzed data consist of linguistic units, such as words and phrases, that convey Indonesian cultural meanings and their equivalents in the Arabic subtitles. The data source is the film "Dear David," directed by Lucky Kuswandi, along with its Arabic subtitle version, available on the Netflix platform. Data collection was conducted through observation, close reading, and systematic note-taking. The analysis process includes data categorization, translation comparison, meaning interpretation, and drawing conclusions regarding the forms of cultural identity negotiation. The findings indicate that the negotiation process involves various aspects, such as material culture, social norms, forms of address, and religious terminology. Differences between linguistic structures and cultural values in Indonesian and Arabic serve as dominant factors influencing translation decisions. The analysis shows that the translator seeks to balance the preservation of the source culture with readability for Arabic-speaking audiences. This study makes a significant contribution to the field of cultural translation and intercultural communication. The implication is that translators must possess a deep understanding of social and cultural contexts and apply strategies such as cultural adaptation, glossing, or annotation to preserve the essence of the message in cross-linguistic transfers.